2011
DOI: 10.1002/art.30229
|View full text |Cite
|
Sign up to set email alerts
|

NF-AT5 is a critical regulator of inflammatory arthritis

Abstract: Objective To investigate the role of nuclear factor of activated T cells 5 (NFAT5), which is known as an osmoprotective transcription factor, in synovial hyperplasia and angiogenesis in rheumatoid arthritis (RA) Methods Expression of NFAT5 was examined in the synovial tissues and synoviocytes of RA patients using immunohistochemistry and Western blot analysis, respectively. The mRNAs of RA synoviocytes and human umbilical vein endothelial cells (HUVEC) transfected with dummy siRNA or NFAT5 siRNA were profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 78 publications
5
107
1
1
Order By: Relevance
“…Recent reports have shown that TonEBP haploinsufficiency reduced inflammatory responses and alleviated pathology of chronic diseases, including rheumatoid arthritis and atherosclerosis. 25,26 Increased TonEBP expression was observed in rheumatoid synovium, where TonEBP haploinsufficiency reduced the cytokine-induced proliferation and angiogenesis. 26 TonEBP in bone marrow-derived cells was required for atherosclerotic lesion formation and macrophage migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have shown that TonEBP haploinsufficiency reduced inflammatory responses and alleviated pathology of chronic diseases, including rheumatoid arthritis and atherosclerosis. 25,26 Increased TonEBP expression was observed in rheumatoid synovium, where TonEBP haploinsufficiency reduced the cytokine-induced proliferation and angiogenesis. 26 TonEBP in bone marrow-derived cells was required for atherosclerotic lesion formation and macrophage migration.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Increased TonEBP expression was observed in rheumatoid synovium, where TonEBP haploinsufficiency reduced the cytokine-induced proliferation and angiogenesis. 26 TonEBP in bone marrow-derived cells was required for atherosclerotic lesion formation and macrophage migration. TonEBP haploinsufficiency led to a significant reduction of aortic lesions in in vivo model of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In several pathologic conditions, NFAT5 exacerbated the formation of damage regions. A lack of NFAT5 retarded the pathogenesis of atherosclerosis by declining the accumulation of MΦs in atherosclerotic lesions [54], and reduced the severity of arthritis with impaired inflammatory cell infiltration by inhibiting the secretion of C-C motif ligand 2 (CCL2) [50], joint destruction, and synovial hyperplasia [55]. NFAT5 also affected cancer proliferation and metastasis by enhancing protumor MΦ2 differentiation [56].…”
Section: The Function Of Nfat5mentioning
confidence: 99%
“…주로 신장 등의 높은 삼투압 환경에서 세포를 보호 하며 여러 기관에서 세포의 생존, 발달 등에 관련된 기능을 한다 [3,18]. 특히 NFAT5는 세포질의 삼투질 농도에 의해 발현 이 조절되며 활막세포와 혈관내피세포의 증식과 분화에 중요 한 역할을 하는 조절인자라고 보고 되어져 있고 [9,30] (Fig. 1A, B 제 시킨 세포에 TNF-α를 처리했을 때에는 TNF-α에 의한 지방 분화 억제효과가 영향을 받지 않았다 (Fig.…”
Section: Nfat5 (Nuclear Factor Of Activated T Cells)는 5종류의unclassified